2022
DOI: 10.1021/acsaem.1c03863
|View full text |Cite
|
Sign up to set email alerts
|

Faceted Crystal Nanoarchitectonics of Organic–Inorganic 3D-Printed Visible-Light Photocatalysts

Abstract: Facet-dependent photocatalytic properties are intrinsic characteristics of several inorganic semiconductors. Herein, faceted crystal engineering and 3D-printing technology have been combined for the fabrication of the first organic–inorganic 3D-printed visible-light photocatalyst prototypes. As a proof-of-concept, two facet crystal nanoarchitectonics have been devised by in situ synthesizing Ag3PO4 nanoarchitectures with tunableamorphous and facetedshapes upon 3D-printed graphene/polylactic acid (G/PLA) nano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 58 publications
(82 reference statements)
0
3
0
Order By: Relevance
“…[119] The reactivity and porosity of the printed product require serious attention. Hence, state-of-the-art works focus [134] on the approach to maximize the photo(electro)catalyst effectiveness whilst unifying them within the polymer matrix. For example, graphene/PLA (G/PLA) polymer is one of the most common filaments used for the FDM process.…”
Section: Fused Deposition Modeling (Fdm)mentioning
confidence: 99%
See 1 more Smart Citation
“…[119] The reactivity and porosity of the printed product require serious attention. Hence, state-of-the-art works focus [134] on the approach to maximize the photo(electro)catalyst effectiveness whilst unifying them within the polymer matrix. For example, graphene/PLA (G/PLA) polymer is one of the most common filaments used for the FDM process.…”
Section: Fused Deposition Modeling (Fdm)mentioning
confidence: 99%
“…Additionally, Munoz et al reported fabrication of 3Dp graphene/PLA filament by FDM, functionalized with Ag 3 PO 4 nanoarchitectures. [134] Their work has also highlighted activation of commercial G/PLA substrate using DMF prior to catalyst deposition, as to achieve electrically active substrate ready for catalyst deposition. The activated 3Dp substrate was then immersed in Ag 3 PO 4 photoactive material, creating an electrostatic interaction between the Ag ion precursor and the oxygenated groups exposed on G/PLA surface.…”
Section: Fused Deposition Modeling (Fdm)mentioning
confidence: 99%
“…Up to date, inorganic semiconductors have been mainly used for designing 3D‐printed photocatalysts with applications in energy and environmental remediation [8] . However, the lack of solubility of such materials in organic solvents results in an inhomogeneous dispersion of the photocatalytic nanoparticles in the thermoplastics that complicates the whole fabrication and extrusion process.…”
Section: Introductionmentioning
confidence: 99%
“…[6c,7] Up to date, inorganic semiconductors have been mainly used for designing 3D-printed photocatalysts with applications in energy and environmental remediation. [8] However, the lack of solubility of such materials in organic solvents results in an inhomogeneous dispersion of the photocatalytic nanoparticles in the thermoplastics that complicates the whole fabrication and extrusion process. Here, we present the design of a 3Dprinted hierarchical porous structure, containing an organic photoactive molecule (EBE), based on a conjugated trimer with a DÀ AÀ D configuration (4,7-bis(thieno[3,4-b][1,4]dioxin-5yl)benzo[c][1,2,5]thiadiazole), for the photocatalytic degradation of persistent organic pollutants and hydrogen generation.…”
Section: Introductionmentioning
confidence: 99%
“…[31][32][33] Recently, various studies have demonstrated the suitability of physically interacting CDs with some inorganic-based 2D materials, such as transition-metal carbides, [34] dichalcogenides, [35] and oxides, [36] to provide unique organicinorganic 0D/2D nanoarchitectonics with enhanced and even new physicochemical characteristics. [37][38][39] Further, calculation studies have shown the benefits of combining germanene and SiC layers to tune the electronic properties of Ge-based derivatives. [40] Consequently, engineering robust organic-inorganic 2D-Ge heterostructures employing covalent chemistry would be a fruitful path toward devising advanced 2D-Ge materials/ devices for task-specific applications.…”
Section: Introductionmentioning
confidence: 99%